INNOVATION DALAM PENGEMBANGAN PRODUK PERBANKAN SYARIAH - Cahyaningtyas, Kartika; Andriyatsari, Rizqa Zuhra; Rizki D, Zulfana (Fakultas Hukum Universitas Sebelas Maret, 2013)
The conditions of Islamic law into national law is now pervasive in all aspects of communityâs life, primarily in the economic aspects of banking. Banking in Indonesia is now currently developing sharia -based banking system. That is because of the needs of Indonesian people who are predominantly Muslim in banking activities that do not violate the rules of Islam, that is usury. All of banking activities ranging from service, the form of transactions, business relationships, and supervision of banking product, can not be separated from Islamic principles. However, the current state of public interest to turn into a sharia bank customers are still lacking. One possible cause is Islamic banking products have not been able to innovate so that the products can not full fill the needs of the community. This is due to the lack of human resources, Â both in terms of product innovation and supervision as well as the specific regulations. Thus, we need a mechanism to oversee the concept of Islamic banking products in order to full fill peoples needs and remain within Islamic principles through the concept of Monitoring Mechanism of Shariah Product Innovation.